Military expenditure and economic growth in the Middle East - Wahid, Latif
This book investigates the role and the impacts of armies and military regimes in the Middle East. It argues that one of the main causes of the slow and stagnated economic development in the region is high military expenditure perpetuated by strong grips of armies on the politics of the region.